DIAGNÓSTICO PRECOCE DO CÂNCER COLORRETAL - Quilici, Flávio Antonio (Revista de Ciências Médicas, 2002)
Large intestine cancer persists as one of the highest incidence in the western world. It is, in the USA, the second in frequency and the first one in death rate as far as malignant diseases are concemed. One person in ten will develop this disease in the USA, which corresponds to 150,000 new cases a year and to 15% of all cancer diagnoses.